Improving corrosion protection of Mg alloys (AZ31B) using graphene‐based hybrid coatings. (6th October 2021) - Afsharimani, Nasima; Talimian, Ali; Merino, Emilia; Durán, Alicia; Castro, Yolanda; Galusek, Dusan
Abstract: In the present work, a study was carried out to compare the morphology and electrochemical properties of pure and graphene‐modified hybrid silica sol–gel coatings deposited on anodized AZ31B magnesium alloys. The precursor solution was prepared using tetraethoxysilane (TEOS) and 3‐glycidoxypropyl‐trimethoxysilane (GPTMS), with the addition of chemically modified graphene nanosheets (GN‐chem). Homogeneous and adherent coatings were obtained using GPTMS‐TEOS (GT) and GPTMS‐TEOS‐GN‐chem (GT/GN‐chem) solutions with uniform thickness around 4 µm. Raman, SEM images and EDS analyses confirmed the presence of graphene nanosheets in the coatings. Potentiodynamic polarization results using 0.05 M NaCl electrolyte solution showed that graphene containing silica coatings significantly improve the corrosion resistance of AZ31B alloys. In addition, a significant passive region was observed for GT/GN‐chem coatings. Abstract : In the present work, we report a comparative study on the morphology and electrochemical properties of pure and graphene‐modified hybrid silica sol–gel coatings deposited on anodized AZ31B magnesium alloys. Anodized AZ31B magnesium alloys coated with sols containing graphene nanosheets (GT/GN‐chem) exhibit better corrosion behavior than graphene‐free samples; this is accounted for by the good quality of the coatings and barrier protection of graphene sheets.